Human Intestinal Mononuclear Phagocytes in Health and Inflammatory Bowel Disease - Caër, Charles; Wick, Mary Jo (Frontiers in Immunology, 2020)
Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, is a complex immune-mediated disease of the gastrointestinal tract that increases morbidity and negatively influences the quality of life. Intestinal mononuclear phagocytes (MNPs) have a crucial role in maintaining epithelial barrier integrity while controlling pathogen invasion by activating an appropriate immune response. However, in genetically predisposed individuals, uncontrolled immune activation to intestinal flora is thought to underlie the chronic mucosal inflammation that can ultimately result in IBD. Thus, MNPs are involved in fine-tuning mucosal immune system responsiveness and have a critical role in maintaining homeostasis or, potentially, the emergence of IBD. MNPs include monocytes, macrophages and dendritic cells, which are functionally diverse but highly complementary. Despite their crucial role in maintaining intestinal homeostasis, specific functions of human MNP subsets are poorly understood, especially during diseases such as IBD. Here we review the current understanding of MNP ontogeny, as well as the recently identified human intestinal MNP subsets, and discuss their role in health and IBD.